Current Developments of RF Energy Harvesting System for Wireless Sensor Networks - Zakaria, Z; Zainuddin, N. A; Husain , M.N; Abd Aziz, M. Z. A; Mutalib, M. A; Othman , A. R (2013)
Energy harvesting or energy scavenging is basically a conversion process of the ambient energy into the electrical energy. The ambient energy exists around us in many different forms including thermal, chemical, electrical and radio frequency (RF). This technique significantly reduces the costs of replacing batteries periodically. Hence, energy harvesting offers various environmental friendly alternative energy sources, which include the vibration, electromagnetic wave, wind energy and solar power. This study will focus on RF energy harvesting that involves the generating of a small amount of the electrical power to drive circuits in wireless communication electronics devices. Recently, wireless sensor network (WSN) has been a crucial part of our daily life. The importance of WSN can be described by the use of sensors in many devices for home security including light sensors, room thermostat and alarm systems. This paper presents an overview and the progress achieved in RF energy harvesting, which involves the integration of antenna with rectifying circuit. Different combinations of antenna and rectifier topologies yield diverse results. Therefore, this study is expected to give an indication on the appropriate techniques to develop an efficient RF energy harvesting system.